In vitro assessment of entomopathogenic fungi Isaria, Lecanicillium species against Coconut black beetle - Saththiya, G.; Mikunthan, T. (Proceeding of the 3rd international conference on Dry Zone Agriculture, 2018)
Coconut black beetle, Oryctes rhinoceros is a serious pest of coconut in Sri Lanka and this is one of most damaging insects to palms in Asia. There is no any method as biological control agent except Baculovirus oryctes to control the beetle population. Nowadays, control methods revolve around treatment based on mechanical, cultural, chemical methods. Mechanical and cultural methods are not such an effective methods. Extensive and inappropriate use of this chemical method can cause serious problems in the environment. Use of Entomopathogenic fungi is an effective and environmentally favorable for the control of pest. The objective of this research was to evaluate the efficacy of entomopathogenic fungi, Isaria fumosorosea, Lecanicillium lecanii on black beetle. Efficacy of the entomopathogenic fungi Isaria fumosorosea, Lecanicillium lecanii was determined by the mortality of black beetle after application of spore counted conidial solution of Isaria fumosorosea, Lecanicillium lecanii on coconut black beetle. Confirmative test was done for the insect cadavers to confirm the causal agent of death. Most effective fungi against coconut black beetle (Oryctes rhinoceros) was Isaria fumosorosea which caused 66.67% mortality at 9.42x109 spores/ml within 13 days after treatment. The Entomopathogenic fungi namely, Isaria fumosorosea and Lecanicillium lecanii have the potential to control the black beetle. Further experiments to be done to check the mortality of black beetle with different spore concentration of Entomopathogenic fungi, Isariafumosorosea and Lecanicillium lecanii in vitro as well as field.
Keywords: Isariafumosorosea; Lecanicillium lecanii; Oryctes rhinoceros; infectivity